2009
DOI: 10.1097/mat.0b013e31819742f0
|View full text |Cite
|
Sign up to set email alerts
|

Single Center Experience With a Low Volume Priming Cardiopulmonary Bypass Circuit for Preventing Blood Transfusion in Infants and Small Children

Abstract: This retrospective study analyzed the current practice of blood transfusion-free open-heart surgery in 536 children weighing 5-20 kg undergoing surgery between 2004 and 2007. A miniaturized cardiopulmonary bypass (CPB) circuit was used (priming volume; 300 ml for the flow rate <1,500 ml/min; 550 ml for the flow rate of 1500-2300 ml/min). Modified ultrafiltration was routinely performed. Criteria for blood transfusion during CPB included a hematocrit of <20% and/or mixed venous oxygen saturation of <65%. Transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 16 publications
2
20
3
Order By: Relevance
“…Additionally, modern surgical techniques such as minimal invasive surgery and the use of modern devices such as argon coagulation have led to a significant reduction of blood loss and transfusion [22]. In addition, the introduction of small-size extracorporeal circulatory devices in cardiac surgery led to a massive reduction in the use of transfusions, especially in small children and newborns [23]. The use of fibrin glue or local hemostyptics elevation of the surgical area [24], arterial embolization, use of antifibrinolytics, and short-term hypertensive provocative therapy prior to wound closure in order to identify bleeding sources can further reduce bleeding and subsequently transfusion requirements [25][26][27].…”
Section: Anesthesia and Surgical Techniquementioning
confidence: 99%
“…Additionally, modern surgical techniques such as minimal invasive surgery and the use of modern devices such as argon coagulation have led to a significant reduction of blood loss and transfusion [22]. In addition, the introduction of small-size extracorporeal circulatory devices in cardiac surgery led to a massive reduction in the use of transfusions, especially in small children and newborns [23]. The use of fibrin glue or local hemostyptics elevation of the surgical area [24], arterial embolization, use of antifibrinolytics, and short-term hypertensive provocative therapy prior to wound closure in order to identify bleeding sources can further reduce bleeding and subsequently transfusion requirements [25][26][27].…”
Section: Anesthesia and Surgical Techniquementioning
confidence: 99%
“…Lechner et al (1) and Seo et al (2) reported postoperative outcomes with the lowbodyweight neonates. Some studies have already shown clinical benefits of reduced priming volume for blood sparing and prevention of acute kidney injury (3,11,14). Many centers with considerable experience in open heart surgery for small children have established their strategy that minimizes the priming volume (1,2,(10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Body weight, preoperative hematocrit, priming volume of the CPB circuit, CPB time, and lowest hematocrit during CPB can predict requirements for blood transfusion during open heart surgery in small infants and neonates [12]. In our case, the patient was supplemented with erythropoietin and took oral iron prior to surgery.…”
Section: Discussionmentioning
confidence: 99%